The role of fisheries in national food security - Tarno, Slamet (International research journal of management, IT and social sciences, 2025)
The fisheries sector plays an important role in supporting Indonesia's national food security by providing a source of high-quality and sustainable animal protein. Capture fisheries and aquaculture not only meet the food needs of the community but also contribute significantly to the economy and welfare of coastal communities. This study employs a literature review method to analyze the contributions, challenges, and efforts to improve the fisheries sector in support of national food security. The results of the study indicate that sustainable fisheries resource management, improved aquaculture technology, and appropriate policy support are essential to maintain the continuity of food supply from the sea. Collaborative efforts among the government, businesses, and the community are crucial to strengthening the fisheries sector's role as a pillar of national food security.